Innovations : a course in natural English - Dellar, Hugh (Thomson Heinle, 2004)
INNOVATIONS is a new three-level general English course for classes looking for new material with a fresh approach. Based on a language-rich, lexical/grammatical syllabus, it starts from the kinds of natural conversations that learners want to have.